2020
DOI: 10.1007/s00404-020-05774-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving the clinical outcomes by extended culture of day 3 embryos with low blastomere number to blastocyst stage following frozen–thawed embryo transfer

Abstract: Purpose This study aimed to investigate whether the extended culture of day 3 (D3) embryos with low blastomere number to blastocyst following frozen–thawed embryo transfer improved the clinical outcomes. Methods This was a retrospective study of clinical data of women undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles in the Tangdu Hospital. The patients were divided into groups with 4–5, 6, 7–9 and > 9 cells based on the blastomere number of D3 embryos. The clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…7 blastomeres. 12 The CPR, IR, and LBR were similar in the elective single morula embryo transfer group and elective single blastocyst embryo transfer group. 21,22 A trend toward higher clinical and ongoing pregnancy rates was noted after day 4 embryo transfers when compared with day 3 embryos in ET cycles.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…7 blastomeres. 12 The CPR, IR, and LBR were similar in the elective single morula embryo transfer group and elective single blastocyst embryo transfer group. 21,22 A trend toward higher clinical and ongoing pregnancy rates was noted after day 4 embryo transfers when compared with day 3 embryos in ET cycles.…”
Section: Discussionmentioning
confidence: 83%
“…6 blastomeres were associated with low IR, CPR, and LBR and high AR compared with those with > 6 blastomeres. 10,12,16 So, the quality of transferred embryos may be another factor contributing to the discrepancy in different studies. One limitation of this study was that patients' characteristic of the number of oocytes from the OPU was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies mentioned above all focused on the effect of the transfer of cleavage-stage embryos with different cell numbers on the clinical outcomes. Li et al [7] found that the implantation and clinical pregnancy rates of ≤6-cell embryos were signi cantly lower than those of 7-9-cell and >9-cell embryos in fresh transfer cycles. However, the implantation and clinical pregnancy rates were no signi cant differences in single blastocyst transfer of ≤6-cell embryos compared with that of ≥7-cell embryos in frozen embryo transfer (FET) cycles.…”
Section: Introductionmentioning
confidence: 99%